2017
DOI: 10.1002/jcp.25669
|View full text |Cite
|
Sign up to set email alerts
|

SirT3 and p53 Deacetylation in Aging and Cancer

Abstract: The mammalian Sirtuins are a family of highly conserved nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylase. The mammalian Sirtuins family has identified seven different types of sirtuin. Sirtuins 3(SirT3) is localized to mitochondria, and is a multiple functional protein deacylase through deacetylating a variety of substrates. Cellular senescence represents a permanent withdraw from cell cycle in response to diverse stress; it is controlled by the p53 and retinoblastoma protein (RB) tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Only 78 genes that are highly expressed in lung are further screened out by Gene (gene-centered information at NCBI) from the 128 genes. Then, 25 differential expression genes were selected as the aging-related genes profile, which, based on previous literatures, were less studied in COPD or considered to be classical ageing-related gene [2732]. In addition, based on the 4 selected COPD-related databases, meta-analysis of the candidate 25 aging-related genes showed that 9 genes (FOXO3, TP53, TGFβ1, MMP2, HDAC1, NUF2, ATG3, AREG and E2F1) were significantly altered in the COPD group compared to the control group (Table 2 and Additional file 3).…”
Section: Resultsmentioning
confidence: 99%
“…Only 78 genes that are highly expressed in lung are further screened out by Gene (gene-centered information at NCBI) from the 128 genes. Then, 25 differential expression genes were selected as the aging-related genes profile, which, based on previous literatures, were less studied in COPD or considered to be classical ageing-related gene [2732]. In addition, based on the 4 selected COPD-related databases, meta-analysis of the candidate 25 aging-related genes showed that 9 genes (FOXO3, TP53, TGFβ1, MMP2, HDAC1, NUF2, ATG3, AREG and E2F1) were significantly altered in the COPD group compared to the control group (Table 2 and Additional file 3).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the levels of SIRT3, a mitochondrial deacetylase, were decreased in high glucose-induced senescent cells [47] and in the aged brain of mice [48]. Reduced levels of SIRT3 lead to increased ROS production and subsequent aging via increase in activated p53 level [49]. In addition, SIRT3 has a pro-proliferative function in human melanoma cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3 is also reported to be a nuclear NAD + ‐dependent histone deacetylase targeting histone 3 lysine 9 (H3K9) and histone 4 lysine 16 (H4K16) during cellular stress conditions . SIRT3 regulates a wide range of important biological functions including metabolic control, neuroprotection, cardiovascular diseases, aging, and cancer, mainly through its deacetylase activity. However, its role in HBV replication remains unexplored.…”
mentioning
confidence: 99%